Budget Targets as Performance Measures: The Mediating Role of Participation and Procedural Fairness - Lau, James (Chong M.); Tan, S. (Emerald Group Publishing Ltd., 2012)
This study revisits the area of reliance on budget to evaluate employee performance. It contributes in several ways. First, it updates this traditional research area making it more relevant to the current debate on the use of financial vis-à-vis nonfinancial measures in multidimensional performance measurement systems. Second, it examines the relationship between reliance on budget and budgetary participation in a manner that is different from that used by prior studies. Instead of treating budgetary participation as a moderating variable, the study examines it as a mediating variable. Specifically, the study hypothesizes that reliance on budget as performance measures affects the extent of employee budgetary participation. Third, it incorporates the recent interest by management accounting researchers in organizational fairness into this research area. It hypothesizes that budgetary participation affects the extent of employees’ perceptions of procedural fairness, which, in turn, influences employee job satisfaction and performance. The structural equation modeling results based on a sample of 152 managers indicate that the use of budget targets for performance evaluation is positively associated with employee job satisfaction and performance. However, much of these effects are indirect via (1) budgetary participation and (2) procedural fairness.